PENGARUH BEBERAPA JENIS PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brassca Rapa L.) - I Made Sukerta; Putu Eka Pasmidi Ariati; Luh Putu Yuni Widyastuti; Fransiskus Diones (Faculty of Agriculture and Business, Universitas Mahasaraswati Denpasar , Kec. Denpasar Utara, Kota Denpasar, Bali 80233, 2024)
The plant below has enough nutrition to promote bodily health. Plants has considerable commercialvalue and prosects to support the efforts of increasing farmer income sources of increased employment opportunities, agribusiness development, increased nutrition in the community. The purpose of this study is 1). To know the effect of certain types of manure on the growth and yield of plant pakcoy 2). To find out which manure provides the best growth and plant output. As for the benefits of this study being 1). It can increase the knowledge of the researcher related to the use of serval typesof manure on the growth and yield of plant 2). Could add to a researcher’s knowledge regarding the use of some types of manure for growth and plant producted. The study was conducted from March 29 to May 27, 2021. The study uses the random group’s (RAK) method of design with 4 kinds of treats (KA) chiken manure 5 tons/ha, (KB) pig manure 5 tons/ha, (KK) goat manure 5 tons/ha, (KS) of cow manure 5 tons/ha. With every treatment repeated 6 times so that the number of treats becomes 24. In the presentation of certain types of manure for the growth and output of the plants plants. Bovine manure 5 tons/ha provides the best growth and effect on all the observable parameters: plant height (cm), number of leaves (baldes), leaf area (cm), root length (cm), total fresh weight (g), and dry weight of the total plant (g